Discontinuous conduction mode approach of ultra-lift DC-DC converter based on three windings coupled inductor - Saeed Hasanzadeh; Milad Asadi; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
These days, DC-DC boost converters play an essential role in a variety of applications. Therefore, a variety of techniques were proposed in the literature to achieve the highest voltage gain. A large number of passive elements are typically used in high-voltage DC-DC converters. Increasing the order of the system would make modeling and controlling the output voltage of the converter more complex. This paper examines an ultra-lift DC–DC converter using a three-winding inductor and a super-lift construction in discontinuous conduction mode (DCM). This converter provides substantial voltage gain by utilizing the three-winding coupling inductor topology without increasing the duty cycle or passive circuit parts. Because the DCM operation mode occurs in the converter, it is necessary to investigate and analyze it. The DCM operation mode of an Ultra-Lift converter is examined in this study, and then simulation results are shown to validate the equations.